What's the Big Deal? How Sales Promotions Displayed by Others Online Can Influence Online and Offline Purchase Intentions. Issue 2 (4th May 2019) - Majid, Kashef; Laroche, Michel
Abstract: When consumers view a sales promotion in a store or online, they have the ability to disseminate it online and inform others. This dissemination may be beneficial to firms because promotions shared online may bypass skepticism toward advertising. This article investigates whether consumers evaluate online sales promotions that users post differently from firm-disseminated posts. We created a unique online environment where consumers could post sales promotions they encountered. Our findings revealed that, over time, those who are most skeptical of advertising had greater intentions to purchase online and lower intentions to purchase in physical stores. Promotions disseminated by consumers may be perceived as advertising, but they can cause consumers to increase their online purchasing.